MOTIVAÇÃO PARA O VOLUNTARIADO: O CASO DO PROJETO DENTISTAS DO BEM - Souza, Luciane Franco de (2013)
Proposal to assess the impact of volunteering on the volunteer. For its construction, developed a literature search that resulted in a data collection instrument to map the perceptions of participating in a volunteer program. Applied to a specific case, in order to test it and to obtain specific information about the program in focus. The choice of program volunteers "Dentists do Bem", is due to the importance of oral health as an affirmation of citizenship. The objective was to analyze by means of a questionnaire the reasons that led him to provide volunteering, and how this initiative affects your professional life as well as to identify the perceptions of volunteer dentists for the effects they perceive as arising from participation in social projects for identifying the effects motivators and inhibitors of this type of participation. The sample for the survey consisted of 50 volunteers determined by the media coordinator of the project Turma do Bem, located near the project site, in the State of São Paulo. The survey found that most respondents act only in TdB more than a social cause , participation is a way of personal satisfaction by the impact that health care cause in the lives of patients and the volunteer. The main motivation is altruism found very generally reported in the literature, which in Brazil is considered as solidarity.